Pegcetacoplan controls hemolysis in complement inhibitor–naive patients with paroxysmal nocturnal hemoglobinuria - Wong, Raymond Siu Ming; Navarro-Cabrera, Juan Ramon; Comia, Narcisa Sonia; Goh, Yeow Tee; Idrobo, Henry; Kongkabpan, Daolada; Gómez-Almaguer, David; Al-Adhami, Mohammed; Ajayi, Temitayo; Alvarenga, Paulo; Savage, Jessica; Deschatelets, Pascal; et al. (Blood advances, 2023)
•Complement inhibitor–naive patients with PNH had greater hemoglobin stabilization and LDH reduction with pegcetacoplan vs control.•Pegcetacoplan’s comprehensive control of hemolysis and favorable safety profile in these patients may help expand the treatment population. [Display omitted] Paroxysmal nocturnal hemoglobinuria (PNH) is a rare disease characterized by complement-mediated hemolysis. Pegcetacoplan is the first C3-targeted therapy approved for adults with PNH (United States), adults with PNH with inadequate response or intolerance to a C5 inhibitor (Australia), and adults with anemia despite C5-targeted therapy for ≥3 months (European Union). PRINCE was a phase 3, randomized, multicenter, open-label, controlled study to evaluate the efficacy and safety of pegcetacoplan vs control (supportive care only; eg, blood transfusions, corticosteroids, and supplements) in complement inhibitor–naive patients with PNH. Eligible adults receiving supportive care only for PNH were randomly assigned and stratified based on their number of transfusions (<4 or ≥4) 12 months before screening. Patients received pegcetacoplan 1080 mg subcutaneously twice weekly or continued supportive care (control) for 26 weeks. Coprimary end points were hemoglobin stabilization (avoidance of >1-g/dL decrease in hemoglobin levels without transfusions) from baseline through week 26 and lactate dehydrogenase (LDH) change at week 26. Overall, 53 patients received pegcetacoplan (n = 35) or control (n = 18). Pegcetacoplan was superior to control for hemoglobin stabilization (pegcetacoplan, 85.7%; control, 0; difference, 73.1%; 95% confidence interval [CI], 57.2-89.0; P < .0001) and change from baseline in LDH (least square mean change: pegcetacoplan, −1870.5 U/L; control, −400.1 U/L; difference, −1470.4 U/L; 95% CI, −2113.4 to −827.3; P < .0001). Pegcetacoplan was well tolerated. No pegcetacoplan-related adverse events were serious, and no new safety signals were observed. Pegcetacoplan rapidly and significantly stabilized hemoglobin and reduced LDH in complement inhibitor–naive patients and had a favorable safety profile. This trial was registered at www.clinicaltrials.gov as NCT04085601.